Adoption and implementation of extended producer responsibility for sustainable management of end-of-life solar photovoltaic panels - S.E. Kabir; M.N.I. Mondal; M.K. Islam; I.A. Alnaser; M.R. Karim; M.A. Ibrahim; K. Sopian; M. Akhtaruzzaman (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Extended producer responsibility has been a policy tool for managing solar photovoltaic waste in European Union countries for approximately a decade. Furthermore, EPR has been widely used in many countries for electronic waste and other forms of waste management. Several studies have recommended this tool to sustainably manage solar photovoltaic waste in countries transitioning to large-scale solar energy usage. Nevertheless, implementing a policy tool varies depending on numerous factors, particularly context differences in developed and developing countries. The research on adopting and implementing this tool for solar photovoltaic waste management is limited in developing countries. Bangladesh requires appropriate regulations to manage the impending waste, which will soon encounter substantial end-of-life solar photovoltaic panel volumes. Therefore, this study investigated the adoption and implementation of the extended producer responsibility policy tool within the context of Bangladesh.METHODS: A comprehensive literature review was conducted to identify the enabling and challenging factors influencing the implementation of this tool. Subsequently, a Likert Scale-based questionnaire incorporating the enabling and challenging factors was framed. A survey targeting stakeholders in the solar photovoltaic sector was then performed. Data analysis involved univariate and bivariate analyses, and Bangladesh was selected as a representative developing country for this study.FINDING: The results revealed that stakeholders in the solar PV industry significantly emphasized (mean > 3) all enabling factors associated with extended producer responsibility for adoption in their country to manage end-of-life photovoltaic panels. This observation signified the importance of adopting and implementing extended producer responsibility to manage the impending disposal of end-of-life solar photovoltaic panels. Among the enabling factors, the public expense reduction (mean = 3.97), user acceptance (mean = 3.89), eco-design encouragement (mean = 4.02), and the local recycling facility with secondary material market establishments (mean = 3.89) emerged as the most crucial factors. The solar photovoltaic waste-specific regulations (mean = 3.72), the absence of a pre-established collection network (mean = 4.20), and weak institutional capacity (mean = 4.03) were identified as challenging factors requiring special attention during this tool adoption. The inter-item correlation matrix analysis for enabling and challenging factors also demonstrated high significance. Moreover, Cronbach's alpha for enabling and challenging factors were 0.885 and 0.749, respectively. This outcome suggested a good and acceptable internal consistency level among the factors.CONCLUSION: Adopting extended producer responsibility was essential in developing countries to ensure the sustainable management of end-of-life solar photovoltaic panels. Nonetheless, successful implementation required addressing specific domestic concerns, such as the absence of a pre-existing waste take-back system and weak institutional capacity. Regulators should also proactively take measures to leverage enabling factors, including gaining users' acceptance, reducing costs, and potentially tapping into secondary material markets. Consequently, this study can assist in formulating appropriate regulations regarding the sustainable management of hazardous end-of-life solar photovoltaic panels. The findings can be utilized in Bangladesh and other countries encountering similar challenges, contributing to environmental preservation and eco-friendly development.